Phytochemicals for the Prevention of Photocarcinogenesis - Montes de Oca, Mary Katherine (Photochem Photobiol, 2017)
Ultraviolet (UV) exposure has an array of damaging effects and is the main cause of skin cancer in humans. Non-melanoma skin cancer (NMSC), including basal cell carcinoma and squamous cell carcinoma, is the most common type of cancer. Incidence of NMSC has increased due to greater UV radiation, increased life expectancy, and other changes in lifestyle; the annual cost of skin cancer treatment in the United States has increased concurrently to around eight billion dollars. Because of these trends, novel approaches to skin cancer prevention have become an important area of research to decrease skin cancer morbidity and defray the costs associated with treatment. Chemoprevention aims to prevent or delay the development of skin cancer through the use of phytochemicals. Use of phytochemicals as chemopreventive agents has gained attention due to their low toxicity and anti-carcinogenic properties. Phytochemicals also exhibit antioxidant, anti-inflammatory, and anti-proliferative effects which support their use as chemopreventive agents, particularly for skin cancer. Preclinical and human studies have shown that phytochemicals decrease UV-induced skin damage and photocarcinogenesis. In this review article, we discuss the selected phytochemicals that may prevent or delay UV-induced carcinogenesis and highlights their potential use for skin protection.